EVALUASI PENGARUH PROYEK PEMBANGUNAN KAWASAN INDUSTRI DAN PELABUHAN INTERNASIONAL (KIPI) TERHADAP PERKEMBANGAN WILAYAH - Agus Subandrio; Doddy Aditya Iskandar (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2022)
The International Port and Industrial Estate Development (KIPI) is a national status project located in North Kalimantan. The KIPI project started in 2016 in accordance with law number 02 of 2016. This international port and industry has an investment value of USD billion 45.98 with an area of ​​±10,000 ha. The problem that usually occurs due to the entry of industrial activities is the occurrence of conflict, so research is needed to find out how much conflict and regional changes occur. The study was conducted using a combination of deductive and qualitative methods with the aim of assessing the spatial, economic and social impacts of industrial and international port development. The influence on the spatial aspect of development which is already large enough to change local revenue by 34.67%. In turn, social and environmental impacts on industrial estates and international ports have an influence that does not lead to conflict.